VALIDITAS MODUL TERINTEGRASI NILAI-NILAI AYAT ALQURAN PADA MATA KULIAH FISIKA UMUM - Yusmanila, Yusmanila (Universitas PGRI Sumatera Barat, 2019)
One of the obligations of lecturers on the education element is to develop creative and innovative learning tools so that students learn optimally and have a positive character. The learning tool that lecturers need to have is teaching material. The teaching materials currently available on the STKIP Adzkia campus are not yet relevant to the Adzkia STKIP vision, which is